2017
DOI: 10.1002/wmh3.217
|View full text |Cite
|
Sign up to set email alerts
|

Health Care for All in Ireland? The Consequences of Politics for Health Policy

Abstract: The Irish health-care system is a complicated mix of public and private providers, with inequitable and unclear routes for health-service users to access and navigate the system. In 2011, the Irish Government committed to significant health reform to develop a universal single-tier health system. In line with other European nations this was to be underpinned by the principle of social solidarity, with equitable access based on need rather than ability to pay. The road to this reform and its recent collapse hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Issues relating to the availability and accessibility of counselling services in Ireland are well recognized. [40][41][42] This clearly needs to be addressed as part of a holistic approach to reducing long-term BZRA use and improving mental healthcare. In the absence of adequate resources, previous users may be able to offer important peer support to current users attempting discontinuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues relating to the availability and accessibility of counselling services in Ireland are well recognized. [40][41][42] This clearly needs to be addressed as part of a holistic approach to reducing long-term BZRA use and improving mental healthcare. In the absence of adequate resources, previous users may be able to offer important peer support to current users attempting discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…One participant who had been referred to a counselling service was still waiting to be contacted by the service. Issues relating to the availability and accessibility of counselling services in Ireland are well recognized 40–42 . This clearly needs to be addressed as part of a holistic approach to reducing long‐term BZRA use and improving mental healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…It is beyond the scope of the current study to identify the exact reasons for the observed trends towards an increasing prevalence of BZRA prescriptions among the younger population groups. Adequate resourcing of mental health services has been a long-standing issue in Ireland which creates difficulties for those with mental health difficulties accessing relevant supports [37][38][39]. Some progress has been made with the introduction of the 'Counselling in Primary Care' service in 2013.…”
Section: Discussionmentioning
confidence: 99%